2008
DOI: 10.1590/s0100-84042008000100015
|View full text |Cite
|
Sign up to set email alerts
|

Composição florística e cobertura vegetal das savanas na região de Alter do Chão, Santarém - PA

Abstract: -(Floristic composition and vegetation cover of the savannas in the "Alter do Chão" region, Santarém-PA) In this study, we determined the floristic composition in 38 plots of 3.75 ha (250 m x 150 m) distributed throughout 30.000 ha of savannas of "Alter do Chão", Santarém Municipality. Our surveys revealed 130 species in 45 families. The only species of dicotoledons that covered 1% or more of the area in the herb-shrub layer were Dioclea bicolor Benth. and Lafoensia pacari A. St.-Hil. Most of the area was cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 23 publications
4
26
1
10
Order By: Relevance
“…The percentage covered by Poaceae observed in the present study was greater than was found previously in western Pará (Magnusson et al 2008), where eight species of Poaceae were identified, with only two of them dominant (Paspalum carinatum and Trachypogon spicatus), although the total coverage of the family was 40.06%. In the savannas within the state of Roraima, Poaceae comprised only 19% of the herbaceous stratum in a survey performed by Takeuchi (1960) and 43.40% in a study conducted by Miranda & Absy (1997).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The percentage covered by Poaceae observed in the present study was greater than was found previously in western Pará (Magnusson et al 2008), where eight species of Poaceae were identified, with only two of them dominant (Paspalum carinatum and Trachypogon spicatus), although the total coverage of the family was 40.06%. In the savannas within the state of Roraima, Poaceae comprised only 19% of the herbaceous stratum in a survey performed by Takeuchi (1960) and 43.40% in a study conducted by Miranda & Absy (1997).…”
Section: Discussioncontrasting
confidence: 84%
“…The Mangaba savanna exhibited the highest coarse sand content and the lowest clay content, potentially influencing water and nutrient availability (Barros et al 2009) and, consequently, the predominance of Axonopus polydactylus (38.47%), a species common to coastal woodlands (Cialdella et al 2006), where the soil is low in clay and organic matter, with low water and nutrient retention capacity (Cuzzuol & Campos 2001). This may be one of the few savanna areas in the Amazon, if not the only area, where two Axonopus species dominate the herbaceous stratum (Takeuchi 1960;Coradin 1978;Bastos 1984;Allem & Valls 1987;Miranda & Carneiro 1994;Miranda & Absy 2000;Baruch 2005;Magnusson et al 2008;Viana & Filgueiras 2008).…”
Section: Discussionmentioning
confidence: 99%
“…being considered generalists able to prosper in a variety of environments (Cavalcanti and Tabarelli 2004). Forty species are known to occur in FF and savanna areas in other regions of the country (Northeast, Central-West and Southeast), and in Alter do Chão 33 of these were found in the FF (Magnusson et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Os poucos estudos existentes desenvolveram suas investigações principalmente com comunidades arbóreo-arbustivas abordando florística e estrutura (Barbosa et al 2005;Miranda et al 2006) ou distribuição espacial em função de fatores ambientais (Miranda et al 2002). Pouca atenção tem sido dada às comunidades de plantas herbáceas, embora seja reconhecido que este componente apresente grande diversidade em campos e savanas da Amazônia (Miranda e Absy 2000; Magnusson et al 2008).…”
unclassified
“…Os resultados desse estudo indicam maior riqueza de plantas herbáceas da família Leguminosae em relação às 15 espécies verificadas na savana de Alter do Chão (PA) por Magnusson et al (2008). Contudo, os resultados dessa investigação são plenamente compatíveis com levantamentos Figura 2 -Dendrograma de dissimilaridade indicando a distância florística (%) entre as parcelas e a distribuição das espécies.…”
unclassified